Dynamic Flavor : Capturing Aroma Using Real-Time Mass Spectrometry - Beauchamp, Jonathan D., editor 645620; ACS Publications (Online service) 645714 (Washington, DC : American Chemical Society, 2021)
Understanding Flavor Component Kinetics. Advanced analytical technologies offer flavor chemists the opportunity to explore and understand complex mixtures in great detail. This work covers three real-time mass spectrometric techniques applied to food-flavor assessments: APCI-MS, PTR-MS, and SIFT-MS. Chapters introduce each technique and review their implementation in key topics of food and flavor science. Latest applications and innovative new developments are outlined in several research chapters. Applications covered in this book include flavor perception and after-taste, food processing, fermentation, spoilage, authentication, and quality control. Analytical chemists in both academia and industry with an interest in flavor release and volatile quality markers will find this work useful. A tasty read for experts and enthusiasts alike.